What Brown v. Board of Education should have said : the nation's top legal experts rewrite America's landmark civil rights decision - Balkin, J. M.; Ackerman, Bruce A. (New York University Press, 2001)
"Brown v. Board of Education, the Supreme Court's landmark 1954 decision ordering the desegregation of America's public schools, is perhaps the most famous case in American constitutional law. Criticized and even openly defied when first handed down, in half a century Brown has become a venerated symbol of quality and civil rights."